Gender Quotas and Board Composition : A Before-and-After Study of CAC 40 Companies Under the Copé–Zimmermann Law (2010–2025) - Buynaya, Alena (2025)
This Bachelor’s thesis examines the impact of mandatory gender quotas on corporate board composition in France, with a particular focus on the Copé–Zimmermann Law and its effects on CAC 40 companies. The study aims to assess whether increased female representation on boards led to substantive structural changes or remained primarily symbolic after legal compliance was achieved. Drawing on agency theory, critical mass theory and stakeholder theory, the thesis analyzes board composition data before and after the implementation of the quota. A longitudinal, firm-level analysis is employed to capture changes in board size, gender balance, and structural characteristics over time. The findings indicate that while the law was highly effective in increasing female representation, the extent of deeper structural transformation varied across firms. The results suggest that achieving numeric gender balance is a necessary but not sufficient condition for meaningful governance change, highlighting the importance of institutional and organizational context in shaping board effectiveness.